Biological silage of shrimp waste fermented with lactic acid bacteria: Use as a biofertilizer in pasture crops and as feed for backyard pigs - Peña García, Petter (2020)
The aim of this study was to determine the viability and use of the biological silage (BE) of shrimp head, molasses and milk fermented with lactic acid bacteria (75-25-5, respectively), providing it as feed for backyard pigs and its leachate as organic fertilizer in the cultivation of maralfalfa grass. It was tested by adding to a base diet for pigs, daily at levels of 0%, 5%, 10 and 15% of the BE and as fertilizer in doses of 300, 500, 700 L/ha (leached) and control (100 nitrogen units) in three applications at 0, 30 and 60 days of installation. Vegetative seed was used in 16 pools of 22 m2, evaluating the main productive parameters at 30, 60 days and at harvest (90 days), 40 growing animals (20 kg) were evaluated in pigs for 35 days. The EB and its leachate were viable and stabilized after 15 days of preparation (pH less than 4.5), presented adequate values as feed for pigs according to the content of protein, fat and ash, as fertilizer it presented amounts of nitrogen, phosphorus and potassium higher than a conventional liquid fertilizer. The use of 700 L/ha presented the best productivity in the study variables, similar to crops installed in cold environments, little precipitation and uncontrolled conditions. The food with the inclusion of BE, were the most efficient, the best economic merit (greater than 97%), BE is a feed alternative for backyard pigs and its leachate is nutritionally suitable for fertilizing forage plants in dry weather.